2012
DOI: 10.1007/s00395-012-0266-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel pathway of NADPH oxidase/vascular peroxidase 1 in mediating oxidative injury following ischemia–reperfusion

Abstract: Vascular peroxidase 1 (VPO1) can utilize reactive oxygen species (ROS) generated from NADPH oxidase (NOX) to catalyze peroxidative reactions. This study was performed to identify a novel pathway of NOX/VPO1 in mediating the oxidative injury following myocardial ischemia reperfusion (IR). In a rat model of myocardial IR, the infarct size, serum creatine kinase (CK) activity, apoptosis, NOX activity, NOX2 and VPO1 expression were measured. In a cell (rat heart-derived H9c2 cells) model of hypoxia/reoxygenation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 41 publications
1
43
0
2
Order By: Relevance
“…In addition, MPO is only expressed in neutrophils and monocytes under inflammatory response and VPO1 is highly expressed in cells of the cardiovascular system,10 therefore, it may be more significant to explore the role of VPO1 in AAA development. Our previous studies demonstrated that VPO1/HOCl pathway‐mediated oxidative stress contributed to hypoxia‐induced pulmonary vascular remodeling, angiotensin II‐induced VSMC proliferation and myocardial ischemia‐reperfusion injury 8, 11, 19. In this study, we find that VPO1 and 3‐Cl‐tyr (a product of HOCl reacting with tyrosine residues) are significantly increased in human aneurysm tissues compared with healthy aortic tissues.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In addition, MPO is only expressed in neutrophils and monocytes under inflammatory response and VPO1 is highly expressed in cells of the cardiovascular system,10 therefore, it may be more significant to explore the role of VPO1 in AAA development. Our previous studies demonstrated that VPO1/HOCl pathway‐mediated oxidative stress contributed to hypoxia‐induced pulmonary vascular remodeling, angiotensin II‐induced VSMC proliferation and myocardial ischemia‐reperfusion injury 8, 11, 19. In this study, we find that VPO1 and 3‐Cl‐tyr (a product of HOCl reacting with tyrosine residues) are significantly increased in human aneurysm tissues compared with healthy aortic tissues.…”
Section: Discussionsupporting
confidence: 49%
“…Our group previously reported VPO1 uses H 2 O 2 to generate HOCl, a highly reactive oxidant, and enhances oxidative stress in the cardiovascular system 18, 19. To study the effect of HOCl generated by VPO1, we examined the levels of 3‐Cl‐tyr, a product of HOCl reaction with tyrosine, by Western blot after H 2 O 2 treatment in cells with VPO1 depletion.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidative stress events are recognized to participate in MIRI processes, ultimately leading to cell apoptosis and death, cell damage, and mitochondrial dysfunction [3,37]. Following a period of ischemia, re-establishment of the oxygen supply will produce an excessive amount of ROS, which triggers oxidative stress and then induces MIRI [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…VPO-1 is a novel family member of peroxidases identified in cardiovascular system in 2008 [39]. VPO-1 is highly expressed in cardiomyocytes, endothelial cells and vascular smooth muscle cells [40,41,42], and thereby referred to vascular peroxidase (VPO). It is a glycosylated heme-peroxidase that is actively secreted into circulating plasma by vascular endothelial cells [39].…”
Section: Discussionmentioning
confidence: 99%